Effect of platinum nanoparticles on morphological parameters of spring wheat seedlings in a substrate-plant system. Issue 1 (October 2015) - Astafurova, T; Zotikova, A; Morgalev, Yu; Verkhoturova, G; Postovalova, V; Kulizhskiy, S; Mikhailova, S
Abstract: When wheat is cultivated in the media contaminated with platinum nanoparticles, the change in the morphological and physiological indexes of wheat seedlings depends on the physico-chemical parameters of the germination substrate. The changes become less pronounced with the decreasing bioaccessability of the nanomaterial in the following order: water suspension – luvisols – phaeozems. Contamination with nanoparticles affects the height parameters and activates the mechanisms protecting the plant from stress. When using wheat seedlings as test organisms for biotesting the environmental safety of NPs, it is advisable to use the following parameters: weight of roots, weight of aerial part, leaf area, and flavonoid content.